Ronde Keperawatan terhadap Pengetahuan Perawat - Harwina, Harwina; Afriani, Tuti; Rachmi, Shanti Farida; Sudaryati, Sudaryati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the implementation of rounds to improve nurses' knowledge at Fatmawati General Hospital. The research method used is a case study. The study's results showed that optimization of the implementation of rounds was carried out in stages, where 12.5% ​​of rooms were found to have implemented nursing rounds but were not yet optimal. Nurses' knowledge was found to have increased through questionnaires related to the definition, implementation of rounds, the role of round officers, and post-rounds rising from 60% to 80%-100%. When viewed from the accuracy of the implementation of rounds, data on the accuracy of rounds was obtained at 90%-95%. In conclusion, there was an increase in nurses' knowledge at Fatmawati General Hospital after the implementation of rounds. Keywords: Knowledge, Nurses, Nursing Rounds